2019
DOI: 10.3390/nu11081708
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adherence to The Mediterranean Diet with Urinary Factors Favoring Renal Lithiasis: Cross-Sectional Study of Overweight Individuals with Metabolic Syndrome

Abstract: Our purpose was to study the relationship of adherence to the Mediterranean diet (MedDiet) with urinary factors that favor the formation of renal calcium and uric acid stones in overweight and obese participants who had metabolic syndrome. This cross-sectional study examined 267 participants. A well-known MedDiet score (range 0–9) was calculated for each patient, and patients were then categorized has having low (≤3), medium (4–5), or high (≥6) adherence to the MedDiet. Baseline characteristics and urinary par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The Mediterranean diet might play an important protective role against urinary stone formation. This was thoroughly demonstrated in a detailed study by Prieto et al, in which the calcium and uric acid urinary crystallization risks were calculated [84]. The authors found that a high consumption of vegetables was the strongest dietary factor for decreased calcium crystallization risk.…”
Section: The Mediterrenean Dietmentioning
confidence: 90%
“…The Mediterranean diet might play an important protective role against urinary stone formation. This was thoroughly demonstrated in a detailed study by Prieto et al, in which the calcium and uric acid urinary crystallization risks were calculated [84]. The authors found that a high consumption of vegetables was the strongest dietary factor for decreased calcium crystallization risk.…”
Section: The Mediterrenean Dietmentioning
confidence: 90%
“…Some dietary styles, such as Mediterranean diet pattern (defined as high consumption of plant-derived foods with monounsaturated to saturated fatty acids and low consumption of meats), are associated with a lower risk of KSD [ [57] , [58] , [59] ]. Several metabolic abnormalities, such as hypercalciuria, hyperoxaluria, hypocitraturia, hypomagnesuria, and hyperuricosuria, are the known risk factors for kidney stone formation.…”
Section: Strategies To Prevent Ksdmentioning
confidence: 99%
“…After a mean follow-up of 9.6 years, there was a 36% reduced risk of incident stones among those with the greatest adherence to a Mediterranean diet (HR 0.64, 95% CI 0.48–87, p = 0.01) [ 123 ]. The benefit of this diet has been postulated to be related to a lower risk of CaOx crystallization risk on this diet [ 124 ]. In contrast, Soldati and co-workers found no association between adherence to a Mediterranean diet and stone events in 478 obese Caucasian subjects [ 125 ].…”
Section: Specific Diet Typesmentioning
confidence: 99%